A biopsychosocial approach violent offending - Choy, Olivia (The Routledge international handbook of juvenile homicide, 2024)
A growing body of research exists investigating the efficacy of interventions to reduce offending by targeting well-documented biological and health risk factors for crime in a benign way. This chapter presents an overview of findings from experimental trials of biologically based treatment and prevention approaches, such as nutritional supplementation, mindfulness, and non-invasive brain stimulation. Consistent with the social neurocrimino-logical perspective on crime, which posits that social factors can sculpt biological functions in a way to shape criminal behavior, psychosocial interventions such as cognitive behavioral therapy can also affect biological factors associated with violence and crime in juvenile and adult offenders. These findings are discussed within a biopsychosocial framework. The extant body of literature shows that it may be possible to target the biological factors underlying violent behavior in non-invasive ways. Accordingly, this chapter highlights the value of considering biological influences on crime in continued efforts to reduce violent offending, including murder. It also includes a brief discussion of the implementation and ethical issues pertaining to biologically based interventions within the criminal justice system.